Analysis of the Impact of AI-Based Accounting Tools on the Accuracy of Financial Reporting for SMEs in Bandar Lampung - Sri Astuti; Lihan Rini PW; M.Muhayin A Sidik; Irawan Irawan (Penerbit Goodwood, 2026)
Purpose: This study aims to analyze the influence of AI-Based Accounting Tools on the accuracy of financial statements among Micro, Small, and Medium Enterprises (MSMEs) in Bandar Lampung, Indonesia. Methodology/approach: This research adopts a quantitative approach using Structural Equation Modeling (SEM-PLS) with SmartPLS 4.0. The sample consists of 206 MSMEs that have adopted at least one AI-based accounting system such as Jurnal.id, Accurate, or QuickBooks. Results/findings: The findings indicate that digital literacy and the level of technological adoption have a positive and significant effect on the effective use of AI-Based Accounting Tools, which in turn enhances the accuracy of financial reporting. Conclusions: Meanwhile, implementation challenges, such as infrastructure and cost limitations, hinder adoption. This study provides strategic implications for policymakers and technology developers to accelerate digital transformation among MSMEs. Limitations: Data from the Ministry of Cooperatives and SMEs (2023) shows that more than 70% of MSMEs in Indonesia do not yet have systematically prepared financial statements. This condition is caused by limited accounting literacy, human resources, and the low adoption of digital technology. Contribution: This study is expected to provide both theoretical and practical contributions to the development of digital accounting literature, as well as offer recommendations for local governments and technology providers to strengthen the digital transformation ecosystem of MSMEs in Indonesia.